2006
DOI: 10.4319/lo.2006.51.1.0257
|View full text |Cite
|
Sign up to set email alerts
|

The methylmercury cycle in Little Rock Lake during experimental acidification and recovery

Abstract: The cycle of waterborne methylmercury (meHg) in Little Rock Lake is characterized by a period of accumulation during summertime (when the lake is warm and open to the atmosphere) and a period of decline during winter (when the lake is sealed by ice). We followed this cycle for 16 yr, during which time the lake was acidified with H 2 SO 4 and then allowed to recover naturally as part of a long-term field experiment on acidic rain. Mass balance was used to quantify meHg sources and sinks during acidification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
0
18
1
Order By: Relevance
“…Furthermore, other factors, including lake chemistry, atmospheric deposition, lake productivity, and fish growth rates, are also associated with latitude and alkalinity, so that several explanations for patterns in time trends are possible. Regional and local differences in walleye Hg trends are likely because of the complex interplay between atmospheric deposition of Hg, lake alkalinity and pH, and factors that affect microbial community composition and activity, such as the nutrient loading from runoff, or climate change (Watras et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other factors, including lake chemistry, atmospheric deposition, lake productivity, and fish growth rates, are also associated with latitude and alkalinity, so that several explanations for patterns in time trends are possible. Regional and local differences in walleye Hg trends are likely because of the complex interplay between atmospheric deposition of Hg, lake alkalinity and pH, and factors that affect microbial community composition and activity, such as the nutrient loading from runoff, or climate change (Watras et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Wisconsin, pH and alkalinity, lake productivity, and fish growth rates all tend to decrease with increasing latitude (Lillie and Mason 1983;Nate 2004). Alkalinity and pH themselves are probably correlated with causative factors such as the activity of sulfate-reducing bacteria leading to increased rates of methyl Hg production (Watras et al 2006). Increased lake productivity and warmer water temperatures in southern Wisconsin lead to faster fish growth rates, which Simoneau et al (2005) have found to be associated with lower Hg concentrations in fish of the same length.…”
Section: Discussionmentioning
confidence: 99%
“…Warm, shallow, organic rich lake sediments are often important zones of net methylation, and the extent of these sediments in a lake may affect the conversion of Hg to MeHg (Bodaly et al 1993;Munthe et al 2007). Further, the presence of an anoxic hypolimnion significantly enhances net MeHg bioaccumulation in stratified lakes (Watras et al 2006). Additional mechanisms may be important for the bioaccumulation of MeHg, such as the overall response of the phytoplankton community and the food chain structure from producers to fish (Gorski et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In our loon data, the second best fitting model for adult blood Hg trends included an interaction between pH and year, suggesting that the rate of change in Hg concentration over time depends on lake pH, with more rapid decreases over time in more acidic lakes (Online Resource 1-parameter estimates in Table 3). The interplay between atmospheric deposition, lake chemistry and other factors that affect microbial community composition, activity and trophic transfer (e.g., Watras et al 2006;Simoneau et al 2005;Chen and Folt 2005) likely leads to spatial differences in loon blood trends. Nevertheless, our biphasic time trend data for Wisconsin loons are largely consistent on a regional scale with contemporaneous trends in waterborne SO 4 and meHg observed in Little Rock Lake.…”
Section: Discussionmentioning
confidence: 99%